Potent anti‐inflammatory properties of HDL in vascular smooth muscle cells mediated by HDL‐S1P and their impairment in coronary artery disease due to lower HDL‐S1P: a new aspect of HDL dysfunction and its therapy. Issue 1 (21st August 2018) - Keul, Petra; Polzin, Amin; Kaiser, Klaus; Gräler, Markus; Dannenberg, Lisa; Daum, Günter; Heusch, Gerd; Levkau, Bodo
ABSTRACT: Dysfunctional HDL is associated with coronary artery disease (CAD), but its effect on inflammation in vascular smooth muscle cells (VSMCs) in atherosclerosis is unknown. We investigated the effect of healthy human HDL and CAD‐HDL on TNF‐α–driven inflammation in VSMCs and examined whether HDL‐associated sphingosine‐1‐phosphate (HDL‐S1P) could modulate inflammation with the aim of designing novel HDL‐based anti‐inflammatory strategies. Healthy human HDL, human CAD‐HDL, and mouse HDL were isolated by ultracentrifugation, S1P was measured by liquid chromatography–tandem mass spectrometry, and TNF‐α–induced inflammation was characterized by gene expression and analysis of NF‐κB–dependent signaling. Mechanisms of S1P interference with TNF‐α were assessed by S1P receptor antagonists, mouse knockouts, and short interfering RNA. We observed that healthy HDL potently inhibited the induction of TNF‐α‐stimulated inflammatory genes, such as iNOS (inducible NO synthase) and MMP9 (matrix metalloproteinase 9), a process that was entirely dependent on HDL‐S1P, as evidenced by loss‐of‐function using S1P‐less HDL and mimicked by genuine S1P. Inhibition was based on suppression of TNF‐α–activated Akt signaling resulting in reduced IkBαSer32 and p65Ser534 NF‐κB phosphorylation based on a persistent phosphatase and tensin homolog activation by S1P through the S1P receptor 2. Intriguingly, S1P suppressed inflammation even hours after initial TNF‐α stimulation. The anti‐inflammatory effect of healthy HDL correlated with HDL‐S1P content and was superior to that of CAD‐HDL featuring lower HDL‐S1P. Nevertheless, therapeutic loading of HDL with S1P completely restored the antiinflammatory capacity of CAD‐HDL and greatly boosted that of both healthy and CAD‐HDL. Suppression of inflammation by HDL‐S1P defines a novel pathophysiologic characteristic that distinguishes functional from dysfunctional HDL. The anti‐inflammatory HDL function can be boosted by S1P‐loading and exploited by S1P receptor‐targeting to prevent and even turn off ongoing inflammation.—Keul, P., Polzin, A., Kaiser, K., Gräler, M., Dannenberg, L., Daum, G., Heusch, G., Levkau, B. Potent anti‐inflammatory properties of HDL in vascular smooth muscle cells mediated by HDL‐S1P and their impairment in coronary artery disease due to lower HDL‐S1P: a new aspect of HDL dysfunction and its therapy. FASEB J. 33, 1482–1495 (2019). www.fasebj.org